Pregunta
\( \left. \begin{array} { c } { \lim _ { t \rightarrow 0 } ( t ^ { 2 } \vec { \imath } + 3 t \vec { \jmath } + \frac { 1 - \cos t } { t } \vec { k } ) } \\ { = \langle [ ? ] , [ \quad ] , [ \quad ] \rangle } \\ { } \end{array} \right. \)
Ask by Washington Cross. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\[
\left\langle 0, \; 0, \; 0 \right\rangle
\]
Solución
To evaluate the limit:
\[
\lim_{t \rightarrow 0} \left( t^2 \vec{\imath} + 3t \vec{\jmath} + \frac{1 - \cos t}{t} \vec{k} \right)
\]
we can examine each component separately.
1. **\(\vec{\imath}\) component:**
\[
\lim_{t \rightarrow 0} t^2 = 0
\]
2. **\(\vec{\jmath}\) component:**
\[
\lim_{t \rightarrow 0} 3t = 0
\]
3. **\(\vec{k}\) component:**
\[
\lim_{t \rightarrow 0} \frac{1 - \cos t}{t}
\]
Using the Taylor series expansion for \(\cos t\) around \(t = 0\):
\[
\cos t = 1 - \frac{t^2}{2} + \frac{t^4}{24} - \cdots
\]
Therefore:
\[
1 - \cos t = \frac{t^2}{2} - \frac{t^4}{24} + \cdots
\]
Dividing by \(t\):
\[
\frac{1 - \cos t}{t} = \frac{t}{2} - \frac{t^3}{24} + \cdots
\]
Taking the limit as \(t \rightarrow 0\):
\[
\lim_{t \rightarrow 0} \frac{1 - \cos t}{t} = 0
\]
Putting it all together, the limit vector is:
\[
\left\langle 0, \; 0, \; 0 \right\rangle
\]
So, filling in the blanks:
\[
\left. \begin{array}{c}
\lim_{t \rightarrow 0} \left( t^2 \vec{\imath} + 3t \vec{\jmath} + \frac{1 - \cos t}{t} \vec{k} \right) \\
= \langle\, 0 \,,\, 0 \,,\, 0 \,\rangle
\end{array} \right.
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
As \( t \) approaches 0, we can evaluate each component of the vector separately. The x-component is simply \( \lim_{t \to 0} t^2 = 0 \). For the y-component, \( \lim_{t \to 0} 3t = 0 \) as well. The z-component involves a special limit: \( \lim_{t \to 0} \frac{1 - \cos t}{t} \). Using L'Hôpital's Rule or recognizing that \( 1 - \cos t \approx \frac{t^2}{2} \) near 0 yields \( \lim_{t \to 0} \frac{1 - \cos t}{t} = 0 \). Putting it all together, we have \( \langle 0, 0, 0 \rangle \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium